Nostalgic Overtones in “The Autumn Cry of the Hawk” by I. Brodsky - O. V. Bogdanova (Научный диалог, 2022)
The article offers a new perspective of the interpretation of the poem by I. Brodsky “The Autumn cry of a hawk” (1975). If the text is traditionally considered as the realization of the theme “the poet and the crowd”, then the nostalgic motifs of “the autumn cry” are highlighted in the work. It is shown that the first years of emigration formed certain milestones in Brodsky’s mind that required “intermediate” results, and the year 1975, the third year of emigration, actualized the motives of the “native nest” in the poet’s mind. However, unlike the usual angles of homesickness, the worldview of the herobird Brodsky outgrows the limits of nostalgic feeling, but acquires the features of an ontological myth about the laws of the existence of the Universe. The motives of the individual’s fate, freedom / lack of freedom of the individual obscure the motives of homesickness in Brodsky’s text, but the latter do not disappear without a trace, but are marked with a number of “American” and “Russian” details, images, word forms. The multiplicity of geographical toponyms (Connecticut, New England, Rio Grande), the redundancy of signs of “alien” reality (13 American states, “English” speech) allow us to explicate the invisible contrast “your own and others’ ”, reinforced by the antitheses “up / down”, “heat / ice”, “North / South”. The distinct plot of the poem (the flight of a hawk to his native places) turns out to be an important semantic entourage that enhances the depth of poetic perception.